EVALUATION OF EVENDO SCORE FOR IDENTIFYING HIGH-RISK ESOPHAGEAL VARICES (The Research of Medical Science Review, 2024)
Liver cirrhosis can cause life-threatening esophageal varices (EV), which cause upper gastrointestinal bleeding. High-risk varices must be identified in cirrhotic patients to prevent severe bleeding and death. Cirrhotics may benefit from EVendo Score for high-risk varices. This study examined the diagnostic accuracy of EVendo Score in predicting high-risk esophageal varices using upper GI endoscopy as the gold standard.Crosssectional study from March 2024 to August 2024 in the Outpatient Gastroenterology Department of Shaheed Mohtarma Benazir Bhutto Medical University (SMBBMU), Larakana. This study was performed on 175 patients by non-probability purposive sampling after taking an informed consent. This study included both male and female patients aged 18–60 years with the diagnosis of liver cirrhosis. The data were statistically analyzed by using SPSS v. 26.0. Receiver operating characteristic (ROC) curve was created, and area under the curve (AUC) was also repoted.The study participants were divided into two groups with esophageal varices (n=74) and those without esophageal varices (n=101). Mean age was slightly higher in the group without esophageal varices (49.46 ± 9.55 vs. 47.39 ± 11.24). In gender distribution the proportion of males was documented as slightly higher in both groups (66.2% in varices group vs. 62.4% in no varices group). The area under the curve (AUC) was noted as 0.849 (95% CI: 0.786–0.912). The optimal cutoff value was found to be ≥ 1.50, with a sensitivity of 98.6% and a specificity of 95.0%.The E/Vendo score is found to be a simple and useful non-invasive tool to diagnose high-risk esophago-gastric varices in cirrhotic patients. It offers a high degree of combined sensitivity and specificity at ideal cut-offs which is important for clinical utility. At very high cutoff values, this is reduced, which means that its use should be limited to thresholds that allow for proper prediction.